Activation of muscarinic cholinoceptor ameliorates tumor necrosis factor‐α‐induced barrier dysfunction in intestinal epithelial cells. Issue 23 (28th October 2015) - Khan, Md Rafiqul Islam; Uwada, Junsuke; Yazawa, Takashi; Islam, Md Tariqul; Krug, Susanne M.; Fromm, Michael; Karaki, Shin-ichiro; Suzuki, Yuichi; Kuwahara, Atsukazu; Yoshiki, Hatsumi; Sada, Kiyonao; Muramatsu, Ikunobu; et al.
Abstract : Impaired intestinal barrier function is one of the critical issues in inflammatory bowel diseases. The aim of this study is to investigate muscarinic cholinoceptor (mAChR)‐mediated signaling for the amelioration of cytokine‐induced barrier dysfunction in intestinal epithelium. Rat colon challenged with TNF‐α and interferon γ reduced transepithelial electrical resistance (TER). This barrier injury was attenuated by muscarinic stimulation. In HT‐29/B6 intestinal epithelial cells, muscarinic stimulation suppressed TNF‐α‐induced activation of NF‐κB signaling and barrier disruption. Finally, muscarinic stimulation promoted the shedding of TNFR1, which would be a mechanism for the attenuation of TNF‐α/NF‐κB signaling and barrier disruption via mAChR. Abstract : A role of mAChR in colonic epithelial barrier function is explored. Stimulation of mAChR ameliorates TNF‐α‐induced barrier damage. The mAChR inhibits TNF‐α‐induced NF‐κB activation and IL‐8 production. The mAChR augments the shedding of TNFR1 ectodomain to attenuate TNF‐α signaling.